2021
DOI: 10.7150/jca.62340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of geriatric nutritional risk index (GNRI) and prognostic nutritional index (PNI) in elderly patients with Diffuse Large B-Cell Lymphoma

Abstract: Background: Geriatric nutritional risk index (GNRI) and prognostic nutritional index (PNI) are associated with prognosis of various malignancies. Although GNRI and PNI indicates prognosis in some clinical settings, the values of GNRI and PNI on the prognosis of geriatric patients with Diffuse Large B‐Cell Lymphoma (DLBCL) is unclear. This retrospective analysis aimed to explore the prognostic values of GNRI and PNI in elderly DLBCL patients. Methods: A total of 133 geriatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Recent evidence showed that PNI was closely associated with clinical outcomes of cancer [ 13 , 14 ] and sepsis [ 15 , 16 ]. However, the prognostic role of PNI in the cases with stroke is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence showed that PNI was closely associated with clinical outcomes of cancer [ 13 , 14 ] and sepsis [ 15 , 16 ]. However, the prognostic role of PNI in the cases with stroke is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As regard to malignancy, two meta-analyses concluded that low GNRI level was correlated with poor overall survival in patients with gastrointestinal malignancy ( 30 ) and lung cancer ( 31 ). Other studies also found its prognostic value in hepatocellular carcinoma ( 32 ), renal cancer ( 33 ), bladder cancer ( 34 ), and lymphoma ( 35 , 36 ). Similarly, these results indicated clinical value of GNRI in nutrition assessment among elderly cancer patients.…”
Section: Discussionmentioning
confidence: 90%
“…All the eligible articles were published between 2018–2022 ( 14 20 ). Three studies were conducted in Japan ( 14 , 16 , 18 ), two in China ( 15 , 19 ), and one each in Taiwan ( 17 ) and Turkey ( 20 ). The sample size was 133–615 (median, 267).…”
Section: Resultsmentioning
confidence: 99%
“…The threshold GNRI was 92-106.26 (median, 96.8). Six studies analyzed thresholds with receiver operating characteristic (ROC) curves (14, [16][17][18][19][20], while one study selected cut-off values according to the literature (15). Five studies were carried out in a single center (14, 15,17,19,20), and two were multicenter trials (16,18).…”
Section: Qualified Article Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation